Application of Differentiated Learning to Increase Student Motivation in Physics Learning at SMAN 1 Situbondo - Vidya Matarani Salma; Aida Nurul Safitri (Experimental Student Experiences, 2023)
This research focuses on determining how the application of differentiated learning can increase students' motivation in learning Physics. This type of research uses a qualitative descriptive analysis research methodology and is conducted in three stages, including pre-learning, the first cycle of learning, and the second cycle of learning. 35 students from SMA Negeri 1 Situbondo's class XI MIPA 3 served as the study's subjects. The data collection technique used was a questionnaire and observation by categorizing students into five categories of learning motivation based on the scores obtained from the questionnaire. The results showed that there is a significant increase in student learning motivation after applying differentiated learning in learning Physics in high school that was proven by the significant increase of the percentage in learning motivation category that was very high from the pre-cycle percentage of 0.00%, then in the first cycle learning increased to 11.43%, and in the second cycle learning increased to 40%. This increase shows that students are enthusiastic and motivated in participating in differentiated learning activities.